Antibacterial Activity of Various Extracts of Averrhoa bilimbi against Multidrug Resistant Bacteria - Prastiyanto, Muhammad Evy; Wardoyo, Fandhi Adi; Wilson, Wildiani; Darmawati, Sri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
The multi-drug resistance (MDR) bacteria is a global health problem that causes high mortality every year. Therefore, novel antibacterial agents are needed from natural biological sources. This research aimed to investigate the antibacterial activities of various crude extracts of Averrhoa bilimbi against MDR bacteria. The antibacterial activity was calculated based on the use agar well diffusion assay and the minimum bactericidal concentration (MBC) using Mueller–Hinton broth in a microdilution method. Bacteria from wells were subcultured using inoculating loop onto a 5% sheep BAP. The best antibacterial activity, calculated as the most widely inhibitory zone and the smallest MBC values. The ethanolic extract showed antibacterial activity against the all MDR bacterial test in the agar well diffusion assay (10-14.5 mm inhibition diameter). The MBC of water extract against ESβL + CR Pseudomonas aeruginosa showed the best antibacterial activity (12.5 mg/mL). The fruit of bilimbi was shown to be potentially developed as antibacterial agents, especially for MDR strains. Further in vivo research and discovery of action mode are needed to shed light on their antibacterial effects. This study can provide new information about the benefits of bilimbi as a source of natural antibacterial againts MDR-bacteria